Applications of magnetic resonance in cancer diagnosis therapy - Baillie-Hamilton, P; Baillie-Hamilton, Paula Frances (1995)
This thesis aims to demonstrate how both clinical benefits and advances in therapeutic knowledge can be derived from the application of nuclear magnetic resonance to cancer research. Contrast enhanced magnetic resonance imaging (MRI) was selected for its sensitivity in detecting breast cancer and was applied to the current problem of diagnosing cancer in scarred breasts. 31P Magnetic resonance spectroscopy (MRS) of calf muscle was used to test for metabolic abnormalities in patients on clinical trials with the novel anti-cancer drug and protein kinase C (PKC) activator bryostatin-1, following reports of severe drug-induced myalgia (muscle pain). 31P MRS of isolated perfused rat hearts was used to examine mechanisms of druginduced toxicity. Twenty four patients with indeterminate breast masses were studied using contrast enhanced MRI, followed by pathological diagnosis. The most reliable pulse sequence for diagnosis was dynamic contrast-enhanced gradient-recalled echo. All carcinomas enhanced significantly, whilst scar tissue enhanced to a lesser degree or not at all. Little or no enhancement therefore reliably excluded cancer. Thirty-three 31P MRS calf muscle exercise studies and twelve nearinfrared spectroscopy studies of the arm were performed in patients on bryostatin-1, before and after the onset of myalgia, with pre-drug studies acting as controls. 31P MRS showed increased phosphodiesters, suggestive of muscle injury and reduced muscle energy metabolism in the recovery from exercise. Muscle vasoconstriction was suggested by both studies. Infusion of bryostatin-1 into isolated perfused rat hearts produced a marked reduction of myocardial function, energy metabolism, pH and coronary flow, compared to controls. β-Adrenoceptor agonists prevented both bryostatin-1 induced vasoconstriction and reduced myocardial function, whereas PKC-inhibition blocked vasoconstriction. This shows that bryostatin-1 alters muscle metabolism in several ways known to result in the production of myalgia. Cardiac monitoring in future clinical studies is suggested as are muscle biopsies.